2015
DOI: 10.4049/jimmunol.1500148
|View full text |Cite
|
Sign up to set email alerts
|

A Haptotaxis Assay for Leukocytes Based on Surface-Bound Chemokine Gradients

Abstract: The migration of leukocytes in response to chemokine gradients is an important process in the homeostasis of the human immune system and inflammation. In vivo the migration takes place on the surface of the endothelium to which the chemokine gradient is immobilized via interaction with glycosaminoglycans. To study leukocyte migration in response to surface-bound chemokines, we generated chemokine gradients by a simple stamping method: agarose stamps were soaked with chemokine solution to form continuous chemok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 72 publications
0
13
0
1
Order By: Relevance
“…Rink et al . 32 recently suggested characterising chemotaxis by calculating the Chemotactic Precision Index (CPI) instead of the more common Forward Migration Index (FMI, also known simply as the Chemotactic Index or as the McCutcheon Index) 38 40 . They claim that CPI is a better indicator of chemotaxis because it reports simultaneously on three aspects of the cell movement: it increases as the cell moves directly toward an end point (directness), it increases if the movement is in the gradient direction (cos 2 ϕ , where ϕ is the angle between FMI and directness), and it decreases if the displacement diverts in other direction (1-|SMI|, where SMI stands for Side Migration Index).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rink et al . 32 recently suggested characterising chemotaxis by calculating the Chemotactic Precision Index (CPI) instead of the more common Forward Migration Index (FMI, also known simply as the Chemotactic Index or as the McCutcheon Index) 38 40 . They claim that CPI is a better indicator of chemotaxis because it reports simultaneously on three aspects of the cell movement: it increases as the cell moves directly toward an end point (directness), it increases if the movement is in the gradient direction (cos 2 ϕ , where ϕ is the angle between FMI and directness), and it decreases if the displacement diverts in other direction (1-|SMI|, where SMI stands for Side Migration Index).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Rink et al . 32 used hydrogel-based microcontact printing to transfer CXCL8 gradients onto a petri dish surface to study neutrophil haptotaxis. While agarose stamping of a diffusion gradient is simple to perform, it results in only a short-lived protein gradient induced by the deposition of thin agarose layers on a substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Although microfluidic devices have been developed specifically to dissect the differential contributions of superimposed soluble and haptotactic gradients to cell migration 37 , this was not possible using our current maze device design. Surface-bound IL-8 has been shown to induce random migration by human neutrophils 38 , 39 . A simpler device was therefore employed to compare the motility induced by soluble and bound gradients.…”
Section: Discussionmentioning
confidence: 99%
“…Secretion and immobilization of soluble IL‐8 on localized GAG‐presenting BECs and nearby connective tissue causes neutrophils to preferentially crawl and invade sites of inflammation. Rink et al, experimentally showed neutrophil CXCR1/CXCR2‐mediated haptotaxis using custom agarose stamps to micropattern IL‐8 binding sites on glass substrates . Using a laser‐assisted protein adsorption method, to reproduce substrate bound formyl‐peptide concentration gradients, formyl peptide receptor (FPR)‐mediated haptotaxis was demonstrated .…”
Section: Reverse Engineering Of the Immune Microenvironmentmentioning
confidence: 99%